Profanity in Social Media: An Analysis of Pragmatic Functions and Politeness Maxims Violation - Mejia, Gil Emanuel A.; Ngo, Cristy Grace A. (CV. Tripe Konsultan, 2024)
This corpus-based study employed sociopragmatic analysis to identify the role of profrane linguistic expressions on social media, specifically Facebook and Instagram, in terms of their pragmatic functions and politeness maxims violations. The pragmatic functions identified are cathartic, abusive, and social functions; while the politeness maxims violations are tact, generosity, approbation, modesty, agreement, and sympathy maxims. This study not only illustrates the functions of profanity on social media but also reveals a pattern of profanity-violating maxims that are more focused on the other than the self-indicating offensive pragmatics behind profanity. However, it is important to note that the findings may not be generalizable to all social media platforms or cultural contexts, and further research is needed to explore these aspects.